2018
DOI: 10.1039/c8nr06156d
|View full text |Cite|
|
Sign up to set email alerts
|

Metal enhanced fluorescence biosensing: from ultra-violet towards second near-infrared window

Abstract: To increase disease survival rates, there is a vital need for diagnosis at very preliminary stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(109 citation statements)
references
References 133 publications
1
103
0
Order By: Relevance
“…Due to the reduced photon scattering and minimal tissue absorption, fluorescence imaging in the NIR window (700–1700 nm) offers increased tissue penetration depths and a better signal‐to‐noise ratio rendering it ideal for biomedical applications. [ 1–7 ] Currently, NIR fluorescent materials mainly comprise quantum dots, [ 8–10 ] lanthanide‐doped upconverting nanoparticles, [ 11–13 ] organic small molecules, [ 14,15 ] and polymer‐based systems. [ 16 ] However, long‐term toxicity and immunogenicity, non‐biodegradability, as well as photo‐instability of these non‐life‐like materials have restricted their translation into clinical applications.…”
Section: Figurementioning
confidence: 99%
“…Due to the reduced photon scattering and minimal tissue absorption, fluorescence imaging in the NIR window (700–1700 nm) offers increased tissue penetration depths and a better signal‐to‐noise ratio rendering it ideal for biomedical applications. [ 1–7 ] Currently, NIR fluorescent materials mainly comprise quantum dots, [ 8–10 ] lanthanide‐doped upconverting nanoparticles, [ 11–13 ] organic small molecules, [ 14,15 ] and polymer‐based systems. [ 16 ] However, long‐term toxicity and immunogenicity, non‐biodegradability, as well as photo‐instability of these non‐life‐like materials have restricted their translation into clinical applications.…”
Section: Figurementioning
confidence: 99%
“…UV and DUV excitations can be utilized to perform Raman spectroscopy on biomolecules that have small Raman cross sections in the visible and NIR regions [6][7][8][9]. Additionally, important biomolecules (such as some amino-acids) have intrinsic fluorescence in the UV region [10], and a platform able to enhance the detection limit thanks to plasmonic effects is highly appealing in biosensing [11][12][13]. Several alternative materials have been investigated during the recent years; among them magnesium [14], gallium [15][16][17][18][19], indium, rhodium [20][21][22][23][24], and aluminum (Al) [4,22,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] The MEF effect is dependent on several factors including nanoparticle size, material, and morphology, as well as the distance between the metal surface and the uorophore. [25][26][27][28]30,31 It has been shown that uorophores placed approximately 5 nm or less from the metal surface are quenched rather than enhanced, with 10 nm shown to be the optimum distance for MEF with enhancement decreasing at greater distances. 27,29 It is important to note that the uorescence intensity will only be enhanced if there is a spectral overlap between the uorophore excitation/emission range and the surface plasmon resonance band of the nanostructure.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28]30,31 It has been shown that uorophores placed approximately 5 nm or less from the metal surface are quenched rather than enhanced, with 10 nm shown to be the optimum distance for MEF with enhancement decreasing at greater distances. 27,29 It is important to note that the uorescence intensity will only be enhanced if there is a spectral overlap between the uorophore excitation/emission range and the surface plasmon resonance band of the nanostructure. [29][30][31] MEF leads to alterations in the quantum yield (Q) and the uorescence lifetime (s) of the uorophore as demonstrated by eqn (1)- (4) where Q is the quantum yield, s is the uorescence lifetime, G is the radiative decay rate, and k nr is the non-radiative decay rate.…”
Section: Introductionmentioning
confidence: 99%